Malaria parasite infection compromises control of concurrent systemic non-typhoidal Salmonella infection via IL-10-mediated alteration of myeloid cell function. - Kristen L Lokken; Jason P Mooney; Brian P Butler; Mariana N Xavier; Jennifer Y Chau; Nicola Schaltenberg; Ramie H Begum; Werner Müller; Shirley Luckhart; Renée M Tsolis (PLoS Pathogens)
Non-typhoidal Salmonella serotypes (NTS) cause a self-limited gastroenteritis in immunocompetent individuals, while children with severe Plasmodium falciparum malaria can develop a life-threatening disseminated infection. This co-infection is a major source of child mortality in sub-Saharan Africa. However, the mechanisms by which malaria contributes to increased risk of NTS bacteremia are incompletely understood. Here, we report that in a mouse co-infection model, malaria parasite infection blunts inflammatory responses to NTS, leading to decreased inflammatory pathology and increased systemic bacterial colonization. Blunting of NTS-induced inflammatory responses required induction of IL-10 by the parasites. In the absence of malaria parasite infection, administration of recombinant IL-10 together with induction of anemia had an additive effect on systemic bacterial colonization. Mice that were conditionally deficient for either myeloid cell IL-10 production or myeloid cell expression of IL-10 receptor were better able to control systemic Salmonella infection, suggesting that phagocytic cells are both producers and targets of malaria parasite-induced IL-10. Thus, IL-10 produced during the immune response to malaria increases susceptibility to disseminated NTS infection by suppressing the ability of myeloid cells, most likely macrophages, to control bacterial infection.